Justice in ‘Allocutio Christini’ of Arnald of Vilanova - Lopéz-Guadalupe Pallarés, Miguel José (De Medio Aevo, 2016)
Arnald of Vilanova’s treatise Allocutio christini, while not being a proper mirror of princes, contains a series of theoretical and practical considerations regarding justice and its application by a king. This is an important text so as to establish Arnald of Vilanova’s political thought, which had an influence on the reign of King Frederick III of Sicily.
Keywords: Justice; Politics; Christian Morality; Arnald of Vilanova; King; Tyrant